MILK MARKETING UNDER COOPERATIVE AND NON-COOPERATIVE MARKETING CHANNELS: EVIDENCE FROM WEST BENGAL - Sarker, Debnarayan; Kumar Ghosh, Bikash (Economic Annals, 2010)
The present study is an attempt to empirically investigate the price spread, marketing costs, marketing margins, marketing efficiency, and profit efficiency among market middlemen under cooperative and non-cooperative marketing channels in the domestic trade market of liquid milk in West Bengal. One of the important findings of this study is that, although the inter-market (and intra-market) price variation for liquid milk under the cooperative marketing agency in not far from uniformity, and all marketing agencies under cooperative channels receive much lower abnormal profit per unit of milk as compared with non-cooperative channels, the former fails to provide much economic benefit, either to the producer or to the consumer, because of the burden of much higher fixed cost per unit of liquid milk.